Bacterial biofilm in chronic lesions of hidradenitis suppurativa. (1st April 2017) - Ring, H.C.; Bay, L.; Nilsson, M.; Kallenbach, K.; Miller, I.M.; Saunte, D.M.; Bjarnsholt, T.; Tolker‐Nielsen, T.; Jemec, G.B.
Summary: Background: Chronic nonhealing or recurrent inflammatory lesions, reminiscent of infection but recalcitrant to antibiotic therapy, generally characterize biofilm‐driven diseases. Chronic lesions of hidradenitis suppurativa (HS) exhibit several characteristics, which are compatible with well‐known biofilm infections. Objectives: To determine and quantify the potential presence of bacterial aggregates in chronic HS lesions. Methods: In 42 consecutive patients with HS suffering from chronic lesions, biopsies were obtained from lesional as well as from perilesional skin. Samples were investigated using peptide nucleic acid–fluorescence in situ hybridization in combination with confocal laser scanning microscopy. In addition, corresponding histopathological analysis on haematoxylin and eosin slides was performed. Results: Biofilms were seen in 67% of the samples of chronic lesions and in 75% of the perilesional samples. The mean diameter of aggregates in lesional skin was significantly greater than in perilesional skin ( P = 0·01). Large biofilms (aggregates > 50 μm in diameter) were found in 42% of lesional samples and in only 5% of the perilesional samples ( P = 0·009). The majority of the large biofilms were situated in sinus tracts (63%) or in the infundibulum (37%). The majority of the sinus tract samples (73%) contained active bacterial cells, which were associated with inflammation. Conclusions: This study suggests that biofilm formation is associated with inflammation of chronic HS lesions. The aggregates most likely occur as a secondary event, possibly due to predisposing local anatomical changes such as sinus tracts (tunnels), keratinous detritus and dilated hair follicles.